2020
DOI: 10.1002/art.41161
|View full text |Cite
|
Sign up to set email alerts
|

Multiparameter Analysis Identifies Heterogeneity in Knee Osteoarthritis Synovial Responses

Abstract: Objective Synovial membrane inflammation is common in osteoarthritis (OA) and increases cartilage injury. However, synovial fluid and histology studies suggest that OA inflammatory responses are not homogeneous. Greater understanding of these responses may provide new insights into OA disease mechanisms. We undertook this study to develop a novel multiparameter approach to phenotype synovial responses in knee OA. Methods Cell composition and soluble protein production were measured by flow cytometry and multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 44 publications
2
22
0
Order By: Relevance
“…Interestingly, the amount of CD4 + T cells expressing CCR5 in SM and SF of our early OA patients is comparably high as previously described in SF of patients with different forms of rheumatic joint diseases such as RA, psoriatic arthritis, and ankylosing spondylitis [ 19 , 20 ]. Nevertheless, one limitation of our study is that CD4 staining of MACS-isolated CD3 + T lymphocytes might be compounded by surface marker cleavage due to the performed enzymatic digestion, as previously described [ 21 ]. Other groups showed lower expression for CCR4 and CCR5 in end-stage OA compared to RA.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the amount of CD4 + T cells expressing CCR5 in SM and SF of our early OA patients is comparably high as previously described in SF of patients with different forms of rheumatic joint diseases such as RA, psoriatic arthritis, and ankylosing spondylitis [ 19 , 20 ]. Nevertheless, one limitation of our study is that CD4 staining of MACS-isolated CD3 + T lymphocytes might be compounded by surface marker cleavage due to the performed enzymatic digestion, as previously described [ 21 ]. Other groups showed lower expression for CCR4 and CCR5 in end-stage OA compared to RA.…”
Section: Discussionmentioning
confidence: 99%
“…These changes have an impact in the articular microenvironment, being crucial for the cartilage repair (33). Labinsky et al (34) stated that OA inflammation is not homogeneous, different inflammatory phenotypes exists and it may influence each patient selection criteria and treatment (28). Thus, the OA treatment requires a multifactorial approach that restrain inflammatory response and provide a pro-chondrogenic microenvironment.…”
Section: Articular Cartilage and Inflammationmentioning
confidence: 99%
“…To date, there are few clinical studies in humans considering macrophage polarization and osteoarthritis (27,34,50,52). Most of them do not access macrophage polarization and when they access, they are in vitro studies with human cells.…”
Section: Macrophages In Oamentioning
confidence: 99%
“…T cells can be broadly divided into helper T cells (T H cells), cytotoxic T cells (Tc cells), and regulatory T cells (Tregs) according to their different functions, and the first two are collectively known as effector T cells. Previous studies have shown that both CD4 + (mainly differentiated into T H cells after activation) and CD8 + T-cell subsets (mainly differentiated into Tc cells after activation) have been found at higher levels not only in synovial fluid and membranes but also in peripheral blood (Haynes et al, 2002 ; Hussein et al, 2008 ; Labinsky et al, 2020 ), which suggests that T H cells and Tc cells are involved in the pathogenesis of OA (Raphael et al, 2015 ). Specifically, OA synovial tissue exhibits increased levels of T H 1 (CD4 + IFN-γ + T cells), T H 17 (CD4 + IL-17 + T cells), and Tc (CD8 + T cells), whereas the synovial fluid has increased levels of T H 1, T H 9 (CD4 + IL9 + T cells) and T H 17 cells.…”
Section: Introductionmentioning
confidence: 99%